Intertemporal remittance behaviour by immigrants in Germany - Giulia Bettin; Riccardo Lucchetti (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
In this paper, we use data from the German Socio-Economic Panel (SOEP) in the 1997-2009 period for a large sample of migrants from 84 countries in order to develop an empirical model for the propensity by migrants to remit. Our model takes into full account the intertemporal aspects of the problem, which has been ignored by a large part of the applied literature, despite its theoretical and empirical importance. We find that most results already established in the empirical literature are confirmed; however, the intertemporal nature of the remittance behaviour emerges very clearly, giving rise to individual patterns which are difficult to synthesize by a simple description. Building on our framework, we find also support for theoretical models which predict different remittance time paths between return and permanent migrants.
Keywords: F24; F22; 330; Migration; Remittances; German Socio Economic Panel